ANALISIS NILAI MORAL PADA ANTOLOGI CERPEN INSPIRATIF “18 CERITA MENGGUGAH” KARYA RORA RIZKY WANDINI, DKK - Agnes Endwitri Sihombing; munthe, dila (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Moral values ​​in literary works in the form of short stories usually reflect the views of the author concerned about moral values. Learning about morals can be obtained from the literary works we read. The purpose of this study is to reveal and examine the moral values ​​contained in a short story. This research is a document analysis research in the form of literature study. The type of research used in this research is descriptive research. The collected data is analyzed, identified, classified and described. The source of data in this research is a literary document in the form of an anthology of inspirational short stories "18 Uploading Stories" by Rora Rizky Wandini. data collection used in this study refers to the structural approach theory according to Levi-Strauss. The results of the study show that the form of values ​​in this short story includes: the form of moral value has three types, namely the first form of moral value in human relations with God has a variant in the form of praying to God, praying and being grateful, the second is a form of moral value in human relations with oneself has the variant of accepting God's destiny, not easily giving up, hard work, discipline and enthusiasm for learning, while the third form of moral value is human relations with other humans in the form of social care, helping parents and empathy. The data found in this study amounted to 33 data.